The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15766/mep_2374-8265.10487
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Course in Computer-Aided Design and Computer-Aided Manufacturing (CAD/CAM) Digital Dentistry: Introduction, Technology and Systems Evaluation, and Exercise

Abstract: Introduction Computer-aided design and computer-aided manufacturing (CAD/CAM) technology is an innovative digital system capable of scanning prepared teeth that are intended to receive crowns, bridges, and inlays and then effectively designing and fabricating restorations. Many dental schools are currently implementing this innovative CAD/CAM technology as part of their curricula and at University of Florida College of Dentistry we created a hands-on elective. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Based on this study's results, the video presentation intervention group showed significantly higher hands‐on simulation exercise assessment scores than the traditional lecture control group. The student's ability to replicate the CAD/CAM exercise requirements can be accredited to the video presentation intervention of faculty demonstrating the exercise procedures with a focus on student‐centered learning 11 . This research was conducted in a hands‐on course in the predental curriculum at the University of Louisville School of Dentistry, USA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this study's results, the video presentation intervention group showed significantly higher hands‐on simulation exercise assessment scores than the traditional lecture control group. The student's ability to replicate the CAD/CAM exercise requirements can be accredited to the video presentation intervention of faculty demonstrating the exercise procedures with a focus on student‐centered learning 11 . This research was conducted in a hands‐on course in the predental curriculum at the University of Louisville School of Dentistry, USA.…”
Section: Discussionmentioning
confidence: 99%
“…The student's ability to replicate the CAD/CAM exercise requirements can be accredited to the video presentation intervention of faculty demonstrating the exercise procedures with a focus on student-centered learning. 11 This research was conducted in a hands-on course in the predental curriculum at the University of Louisville School of Dentistry, USA. Perhaps providing students with a hands-on video demonstrating the simulation exercise steps allowed for easier comprehension of the exercise steps rather than a static PowerPoint presentation.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…This technology is evolving into the industrial IoT, where machines can communicate with each other in real-time for the precise treatment process, resulting in high-quality treatment and surgery with minimal time waste. 9 10 Health care workers can quickly review the procedure and tests performed to better treat patients. Dentistry devices, with the help of the Internet, function as a Cyber-Physical System where the information contained within the devices via sensors is more valuable than the devices themselves.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is evolving into the industrial IoT, where machines can communicate with each other in real-time for the precise treatment process, resulting in high-quality treatment and surgery with minimal time waste. 9,10 Health care workers can quickly review the procedure and tests performed to better treat patients. Dentistry devices, with the help of the Internet, function as a Cyber-Physical System where the information contained within the devices via sensors is more valuable than the devices themselves.…”
Section: Introductionmentioning
confidence: 99%